THE EFFECT OF USING EMAIL ON ENHANCING IRANIAN EFL LEARNERSâ€™ GRAMMAR DEVELOPMENT - Seyed Jalal Abdolmanaï¬-Rokni Golestan Un (University of Kuningan, 2013)
Abstract: There has been much debate over the use of computers and the internet in foreign language teaching for more than two decades. Education, especiallyforeign language teaching, has to adapt and renew itself to be compatible with the globalized world. The purpose of this study was to examine the effect of using email on improving EFL learners' grammar development and to highlight the beneï¬ts of using email in an EFL grammar class.The participantsof the study were 52 female students, aged 1318 who were randomly assigned to an experimental and control group. Each group consisted of 26 participants. The course lasted for three weeks and was held in one of the institutes in Gorgan, Iran. Theexperimental group sent their assignments through emails in addition to the traditional class activities but the control groupreceiving a placebo had the traditional class and assignments were handed in hard copies.For measuring the grammar proï¬ciency, a pretest and posttest was administered to both groups. The pretests and posttests were tests based on the materials covered in the class.The resultsOf the study show that the experimental group outperformed the control group in the posttest.Keywords: electronic mail, EFL, grammar development, e-learning